Workplace violence by specialty among Peruvian medical residents - Nieto-Gutierrez, Wendy (2018)
Objective To determine the prevalence of workplace violence among Peruvian medical residents and to evaluate the association between medical specialty and workplace violence per type of aggressor. Methods This was a cross-sectional secondary analysis that used data from the Peruvian Medical Residents National Survey 2016 (ENMERE-2016). The outcome of interest was workplace violence, including physical and verbal violence, which were categorized according to the perpetrator of violence (patients/relatives and worker-to-worker). Primary exposure was the medical specialty, categorized as clinical, surgical, and other specialties. To evaluate the associations of interest, we estimated adjusted prevalence ratios (PR) with their respective 95% confidence intervals (95% CI) using Poisson regression models with robust variances. Results A total of 1054 Peruvian medical residents were evaluated. The mean age was 32.6 years and 42.3% were female. Overall 73.4% reported having suffered of workplace violence sometime during the residency, 34.4% reported violence from patients/relatives, and 61.1% reported worker-to-worker violence. Compared with clinical residents, surgical residents had a lower prevalence of violence from patients/relatives (PR: 0.71; 95% CI: 0.59–0.87), but a higher prevalence of worker-to-worker violence (PR: 1.11, 95% CI: 1.01–1.23). Conclusion Nearly three quarters of medical residents reported having suffered workplace violence sometime during their residency. Compared with clinical residents, surgical residents had lower rates of violence from patients/relatives, but higher rates of worker-to-worker violence; while residents from non-clinical and non-surgical specialties had a lower prevalence of both types of violence.